2016
DOI: 10.1002/bdra.23492
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygosity of a paternal submicroscopic deletion and a maternal missense mutation in POR gene: Antley‐bixler syndrome phenotype in three sibling fetuses

Abstract: To the best of our knowledge, these sibling fetuses add to the few reported cases of ABS, caused by a combination of a SNV and a CNV in the POR gene. The detailed description of the pathologic and radiographic findings of second trimester fetuses affected with ABS adds novel knowledge concerning the early ABS phenotype, in lack of previous relevant reports. Birth Defects Research (Part A) 106:536-541, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The mutation c.1370G > A (p.Arg457His) has been detected in patients diagnosed with Antley-Bixler syndrome [20, 21]. The other mutations have also been reported in recent years [22, 23]. The mutation c.744C > G (p.Tyr248*) is a nonsense mutation that prematurely terminates the encoding of the POR protein at amino acid 248 (the unmutated protein is 680 amino acids long).…”
Section: Discussionmentioning
confidence: 99%
“…The mutation c.1370G > A (p.Arg457His) has been detected in patients diagnosed with Antley-Bixler syndrome [20, 21]. The other mutations have also been reported in recent years [22, 23]. The mutation c.744C > G (p.Tyr248*) is a nonsense mutation that prematurely terminates the encoding of the POR protein at amino acid 248 (the unmutated protein is 680 amino acids long).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our patient in this study carried compound heterozygosity of a p.R457H missense variant and a novel exon 5 deletion in the POR gene, manifesting as severe ABS malformations, cardiac defects, and early demise in infancy. In another study, severe dysmorphic and skeletal malformations were found in three sibling fetuses with compound heterozygosity in the POR gene; one mutation was a copy number deletion, and the other was a p.A287P missense mutation (41).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the analysis of the FAD binding domain reveals the presence of 10 POR mutations (Y326D, L374H, M408L, G413S, R457H, Y459H, R498P, A503V and G504R) ( Figure 5 ). In this group, R457H is the most prevalent mutation found in the Asian population, especially Japanese individuals, presenting with clinical phenotypes varying from mild to severe [ 3 , 13 , 15 , 16 , 18 , 19 , 20 , 21 , 24 , 25 , 27 , 29 , 41 , 42 , 43 , 47 , 48 , 49 , 53 ]. The R457 is located at the binding site of FAD where it closely interacts with the FAD cofactor ( Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…In this group the A287P mutation commonly found in the Caucasian population accounted for 40% residual activity of POR. The residue A287 plays an important role in stabilizing the beta-sheet structure ( Figure 7 D), and its substitution with Proline would have deleterious effects on the beta-sheet secondary structure, resulting in severe bone defects and sexual development disorders as seen in PORD patients [ 3 , 8 , 13 , 15 , 17 , 18 , 22 , 30 , 32 , 35 , 36 , 37 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%